Analysis of a chemotaxis operon from Rhodospirillum centenum. - Jiang, Z Y (1997)
A chemotaxis gene cluster from the photosynthetic bacterium Rhodospirillum centenum has been cloned, sequenced, and analyzed for the control of transcription during swimmer-to-swarm cell differentiation. The first gene of the operon (cheAY) codes for a large 108-kDa polypeptide with an amino-terminal domain that is homologous to CheA and a carboxyl terminus that is homologous to CheY. cheAY is followed by cheW, an additional homolog of cheY, cheB, and cheR. Sequence analysis indicated that all of the che genes are tightly compacted with the same transcriptional polarity, suggesting that they are organized in an operon. Cotranscription of the che genes was confirmed by demonstrating through Western blot analysis that insertion of a polar spectinomycin resistance gene in cheAY results in loss of cheR expression. The promoter for the che operon was mapped by primer extension analysis as well as by the construction of promoter reporter plasmids that include several deletion intervals. This analysis indicated that the R. centenum che operon utilizes two promoters; one exhibits a sigma 70-like sequence motif, and the other exhibits a sigma 54-like motif. Expression of the che operon is shown to be relatively constant for swimmer cells which contain a single flagellum and for swarm cells that contain multiple lateral flagella.